Three-step PCR mutagenesis for 'linker scanning'. - Li, X M (1993)
'Linker scanning' has been used as an efficient method for systematically surveying a segment of DNA for functional elements by mutagenesis. A three-step PCR method was developed to simplify this process. In this method, a set of 'mutation primers' was made with 6 to 8 base substitutions in the center of the primers. In the first PCR reaction, these 'mutation primers' are paired with an 3' primer from the opposite end of the analyzed sequences to form a 'ladder' of fragments containing the base pair substitutions. These are used as templates in the second PCR with the 3' primer as the only primer to generate single stranded sequences, which are used as primers in the third PCR paired with an 5' primer to complete the mutagenesis. We have tested the method in a mutation screen of the steroid sulfatase promoter. Its application to general site specific mutagenesis is discussed.